2-Ethylhexyl Diphenyl Phosphate Affects Steroidogenesis and Lipidome Profile in Human Adrenal (H295R) Cells - Negi, Chander K; Gadara, Darshak; Bajard, Lola; Spáčil, Zdeněk; Blaha, Ludek (Chemical research in toxicology, 2025)
The ever-increasing use of chemicals and the rising incidence of adverse reproductive effects in the modern environment have become an emerging concern. Several studies have shown that environmental contaminants, such as organophosphate flame retardants (OPFRs), negatively impact reproductive health. To evaluate the potential endocrine-related adverse reproductive effects of widely used and priority-listed compound 2-Ethylhexyl diphenyl phosphate (EHDPP), we characterized its effects on adrenal steroidogenesis in human adrenocortical (H295R) cells. The cells were exposed to EHDPP (1 and 5 μM) for 48 h, and the production of hormones, including progesterone, androstenedione, testosterone, estradiol, cortisol, and aldosterone, was measured. In addition, LC-MS/MS-based lipidomics analysis was done to quantify intracellular lipid profiles, and transcriptional assays were performed to examine the expression of genes related to corticosteroidogenesis, lipid metabolism, and mitochondrial dynamics. Our findings indicate that EHDPP disrupts hormone regulation in vitro, as evidenced by increased estradiol, cortisol, and aldosterone secretion. The expression of key corticosteroidogenic genes (CYP11B2, CYP21A1, 3β-HSD2, and 17β-HSD1) was upregulated significantly upon EHDPP exposure. Intracellular lipidomics revealed EHDPP-mediated disruption, including reduced total cholesterol ester, sphingolipids, and increased phospholipids, triglyceride species, and saturated-monounsaturated lipids subspecies. These alterations were accompanied by decreased ACAT2 and SCD1 gene expression. Moreover, a shift in mitochondrial dynamics was indicated by increased MF1 expression and decreased FIS1 expression. These data suggest that EHDPP disrupts adrenal steroidogenesis and lipid homeostasis, emphasizing its potential endocrine-disrupting effects.
Keywords: steroidy; nadledviny; metabolismus lipidů; organofosfáty; Humans; lipidomika; lidé; Steroids; Organophosphates; Lipid Metabolism; Lipidomics; Adrenal Glands